Transcription of the folC gene encoding folylpolyglutamate synthetase-dihydrofolate synthetase in Escherichia coli. - Bognar, A (1989)
The folC gene of Escherichia coli is cotranscribed with an upstream gene from two promoters located in the noncoding region 5' to the coding sequence of the upstream gene. Virtually all of the expression of the folC gene product, folylpolyglutamate synthetase-dihydrofolate synthetase, is therefore due to the upstream gene promoters. No promoter activity was found in the coding sequence of the upstream gene or in the 72-base-pair noncoding region between the two genes. It is shown that a third gene, which may overlap the coding sequence of the folC gene by 8 base pairs at the 3' end, nevertheless, has an promoter independent from that of the upstream gene-folC operon. These results contrast with those presented by Nonet et al. (M. L. Nonet, C. C. Marvel, and D. Tolan, J. Biol. Chem., 262:12209-12217, 1987), who concluded that folC was cotranscribed with the gene at its 3' end and the gene upstream to folC was cotranscribed with the gene(s) further upstream. A stable stem-loop structure resembling a rho-independent terminator is present within the noncoding region between the upstream gene and the folC gene. Folypolyglutamate synthetase expression is 6- to 15-fold lower than that of the upstream gene product, suggesting that the stem-loop terminates some of the transcription from the upstream gene promoter. We found by deletion mutagenesis and cloning sequences containing the stem-loop structure into a termination reporter plasmid that this stem-loop does not act as an effective terminator of transcription. We also found that the stem-loop does not protect the upstream gene message from degradation, since expression of the upstream gene product in maxicell experiments is the same whether the stem-loop structure is present or deleted.